Pengaruh Penghargaan Finansial, Pelatihan Profesional, Pengalaman Magang, Motivasi dan Kemajuan Teknologi terhadap Minat Mahasiswa Akuntansi dalam Berkarir Sebagai Akuntan Publik - Nabilla Viona Franycea; Herawansyah; Adi Saputra, Danang (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study investigates the determinants that influence the tendency of accounting students to choose a career as a public accountant. The independent variables in this study include financial rewards, professional training, internship experience, motivation, and technological advances. This study uses quantitative research methodology, specifically using surveys as the main data collection instrument. A total of 151 accounting students from Bengkulu Province participated in this study. This study used a purposive sampling strategy to select participants who met the criteria of having completed the audit course. In addition, various statistical studies were used to assess the influence of these factors on students' propensity to pursue a career in public accounting. The findings show that students' propensity for a career in public accounting is not affected by factors such as professional training, internship experience, or financial rewards. Instead, students' career interest in public accounting is influenced by motivation and technological advancement. These findings are supported by theories of motivation and expectations of professional choice. This study offers important insights for educators and policy makers to consider these factors when developing initiatives and regulations targeted at attracting and retaining accounting students.